Compartilhar para chegar: fatores de escolha para usos de serviços de modalidade compartilhados e privados na cidade de São Paulo - Miranda, Daniela Cunha Fernandes (2019)
Faced with the need for locomotion and the lack of infrastructure of urban mobility in large cities, consumers are increasingly seeking alternatives and sharing roads and vehicles in traffic. Even with the growing importance of sharing either services or goods (BOSTMAN.ROGERS.2011), literature has been little explored on this subject. From this scenario the Collaborative Economy supports and supports the studies of this dissertation that aims to identify the profiles of the users of transport by shared and private application in the city of São Paulo, listing factors that make this service relevant or not for this consumer . To reach the results, a qualitative approach was used, with in-depth interviews with 22 people, users of Uber X and Uber Juntos applications, aged between 22 and 54 years. The results point to two user profiles; a more sharing, who has collaborative habits in his day to day and the other less sharing, that gives priority to services with more privacy and individuality. Among the most cited factors for engagement in the shared service, Confiança appears more prominently and is also pointed as the main reason for the refusal to use this type of service. Factors such as price, quality and socialization are also among the principles pointed out for engagement in shared mobility and sustainability does not appear as a potential enabler for the choice among respondents.